Problems of Novice Scholl Principals - Keskinkılıç Kara, Sultan Bilge (My University, 2019)
The aim of this study is to determine the problems faced by the novice school principals in Başakşehir district of Istanbul and to present the solution suggestions of them. The participants of this study, which were used as a qualitative research method, consisted of 60 novice school principals. The data collected by using semi-structured interview forms were analyzed with descriptive analysis method. The problems experienced by the novice school principals and the solutions of these problems were resolved by determining the dimensions of the school administration, other managers, the education process, teachers, students, ministries, provincial, district managers, and parents and by thematizing the answers given by the principals. As a result of this research, it was revealed that the problems such as low level of professional competence, slowness of bureaucratic works, negative attitudes towards school administrators, problems in rewarding system, problems in communication, inadequacy of legal regulations, problems in employee rights, problem of merit system, having to deal with unfounded complaints, paperwork increasing workload, other institutions and organizations avoiding taking responsibility, insufficiency of physical and material impossibilities, problems caused by parents, insufficient in-service training, problems with use of buildings, lack of belonging to teachers and lack of belonging, lack of sense of belonging and discipline had negative effects on school principals. It is determined that novice principals have expectations about extension of legal rights by new legislative arrangements, increasing in-service trainings before starting principal position, awards and performance system innovations, sanctions against unfounded complaints, increasing training for families, improvement in personal rights, and merit-based assignment in appointments.
Keywords: School Management; Educational Management; School Principals; Okul Yönetimi; Eğitim Yönetimi; Okul Müdürü